COVID-19 Prevention Practices and Associated Factors among Diabetes and HIV/AIDS Clients in South-Wollo Zone, Ethiopia: A Health Facility-Based Cross-Sectional Study - Ademas A; Adane M; Keleb A; Berihun G; Lingerew M; Sisay T; Hassen S; Getachew M; Tesfaw G; Getaneh Feleke D; Addisu E; Berhanu L; et al. (Journal of Multidisciplinary Healthcare, 2021)
Ayechew Ademas,1 Metadel Adane,1 Awoke Keleb,1 Gete Berihun,1 Mistir Lingerew,1 Tadesse Sisay,1 Seada Hassen,1 Melaku Getachew,1 Getu Tesfaw,2 Dejen Getaneh Feleke,3 Elsabeth Addisu,4 Leykun Berhanu,1 Masresha Abebe,1 Adinew Gizeyatu,1 Habtemariam Abate,5 Atimen Derso1 1Department of Environmental Health, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 2Department of Pharmacy, College of Health Science, Debre Tabor University, Debre Tabor, Ethiopia; 3Department of Pediatrics and Child Health Nursing, College of Health Science, Debre Tabor University, Debre Tabor, Ethiopia; 4Department of Public Health, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 5Department of Environmental Health Regulatory Directorate, Addis Ababa Food Medicines and Health Care Control Authority, Addis Ababa, EthiopiaCorrespondence: Ayechew Ademas Email aayechew19@gmail.comBackground: Coronavirus-2019 (COVID-19) is affecting many people. Chronic patients are highly vulnerable to contracting an infection. Most people recover within a week, but chronic patients can face severe illness or death. The increasing of cases, complications, and mortality demands compulsory preventive measures. Therefore, this study was designed to identify major preventive practices and associated factors.Methods: A facility-based cross-sectional study was employed from November to December 2020 among diabetics and HIV/AIDS follow-up clients in Dessie referral hospital. Data were entered into EpiData manager 4.6.0 version and exported to Statistical Package for Social Science (SPSS) version 25.0 for data cleaning and analysis. Logistic regression analysis was done and an adjusted odds ratio (AOR) with its 95% confidence interval (CI) was used for determining the strength of association.Results: Data were collected from 426 participants with a mean age of 46.54 years. The overall poor prevention practice rate of COVID-19 among diabetic and HIV/AIDS follow-up clients was 68.8% 95% CI (64.6– 72.8%). Factors significantly associated with poor prevention practice were femaleness (AOR; 1.61; 95% CI; 1.03– 2.51), illiterate [AOR; 2.59; 95% CI; 1.33– 5.09]), family size greater than four (AOR; 2.06; 95% CI; 1.32– 3.23), absence of health professional in the household (AOR; 1.79; 95% CI; 1.13– 2.84), not having health insurance (AOR; 1.85; 95% CI; 1.18– 2.89) and urban residence (AOR; 0.38; 95% CI; 0.18– 0.79).Conclusion: The overall proportion of prevention practice towards COVID-19 among diabetic and HIV/AIDS follow-up clients was poor. Illiteracy, having a family size greater than four, not having health professionals in the household, not having health insurance and urban residency were associated with poor prevention practices. Therefore, continuous health educations about good preventive behavioral practice should be enhanced by the health professionals.Keywords: behavioral practice, COVID-19, Ethiopia, prevention